Molecular characterization of wheat dwarf virus isolates from Serbia based on complete genome sequences - Stanković, Ivana; Zečević, Katarina; Ristić, Danijela; Vučurović, Ivan; Krstić, Branka (Frontiers in Microbiology, 2024)
IntroductionWheat dwarf virus (WDV), the species Mastrevirus hordei of the genus Mastrevirus in the family Geminiviridae, is a cereal virus commonly detected in several European, African and Asian countries that causes economic losses.MethodsIn the spring of 2019, a severe outbreak of wheat dwarfing and yellowing was observed in many winter wheat crops across Serbia. A total of 161 samples were tested for the presence of WDV and other common wheat viruses using double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA). To obtain the complete genome of 23 selected isolates, several overlapping segments of the WDV genome were amplified and sequenced. A phylogenetic tree was constructed using the whole genome sequences of the WDV isolates identified in this study and 40 selected sequences from GenBank.Results and discussionThe results of DAS-ELISA indicated the presence of WDV in all samples collected from 21 sites in all nine districts surveyed. Further molecular characterization based on complete genome sequencing of 23 selected isolates showed that the Serbian WDV isolates had low nucleotide diversity and were closely related to wheat-infecting isolates from Europe, suggesting the presence of wheat-adapted forms of WDV in Serbia. The constructed phylogenetic tree revealed that Serbian isolates grouped in clade E within the wheat-adapted forms. This study provided the first insight into the genetic structure of WDV in Serbia based on its whole genome sequence. Further studies on the vector biology and population dynamics are needed to better understand the factors influencing the emergence and spread of WDV under local agroecological conditions.